by what no should (-6)^-1 be multiplied so the product is 27^-1
Answers
Answered by
7
Answer:
Let the required no. be 'x'
A/c to given conditions
==> x * ( - 6 ) ^ - 1 = 27 ^ -1
==> x = - 6/27
==> x = - 2 / 9
Answered by
1
Answer: -2/9
Step-by-step explanation:-
(-6)^-1 x y = 27^-1
POWERS ARE NEGATIVE SO WE WILL DO RECIPROCAL SO THAT WE GET A POSITIVE POWER:-
= (-1/6)^1 = -1/6; ( -1/27)^1= 1/27
let the unknown no. be y
-1/6 x y= 1/27
-1y= 1/27 x 6= -2/9
TO CHECK:-
-1/6 x -2/9= 2/54= 1/27=(27)^1
Similar questions